Kaarina Kailo, Sauna Culture, Sweat and Spirituality: On the architectonics and cosmology of sacred space - Bartlett, Elizabeth Ann (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2026)
Elizabeth Bartlett offers a review of Kaarina Kailo's book Sauna Culture, Sweat and Spirituality: On the architectonics and cosmology of sacred space (Springer, 2025).